2019
DOI: 10.1212/cpj.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Movement disorders in early MS and related diseases

Abstract: BackgroundLittle is known about the true prevalence and clinical characteristics of movement disorders in early multiple sclerosis (MS) and related demyelinating diseases. We conducted a prospective study to fill this knowledge gap.MethodsA consecutive patient sample was recruited from the MS clinic within a 1-year-period. Patients diagnosed over 5 years before the study start date were excluded. Each eligible patient was interviewed by a movement disorder neurologist who conducted a standardized movement diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 18 publications
2
33
1
Order By: Relevance
“…Disorders of fluid, electrolyte, and acid-base as a category of comorbid metabolic disturbance also commonly occur in patients with heart diseases or renal failure and may also reflect poor diet, fluid intake, or swallowing difficulties in severe MS. 28 Indeed, another reported finding is nausea and vomiting, which could contribute to metabolic disturbance. Finally, abnormal movement was a reported finding that warrants targeted investigation, particularly given report of increased frequency of movement disorder even early in MS. 29 Although we set out to investigate the comorbidity burden associated with MS severity, we found an interesting inverse association between MS severity and certain cancers, including benign neoplasm of the skin. Prior studies reported a lower incidence of all-cause cancers among people with MS relative to matched general population.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Disorders of fluid, electrolyte, and acid-base as a category of comorbid metabolic disturbance also commonly occur in patients with heart diseases or renal failure and may also reflect poor diet, fluid intake, or swallowing difficulties in severe MS. 28 Indeed, another reported finding is nausea and vomiting, which could contribute to metabolic disturbance. Finally, abnormal movement was a reported finding that warrants targeted investigation, particularly given report of increased frequency of movement disorder even early in MS. 29 Although we set out to investigate the comorbidity burden associated with MS severity, we found an interesting inverse association between MS severity and certain cancers, including benign neoplasm of the skin. Prior studies reported a lower incidence of all-cause cancers among people with MS relative to matched general population.…”
Section: Discussionmentioning
confidence: 96%
“…Disorders of fluid, electrolyte, and acid-base as a category of comorbid metabolic disturbance also commonly occur in patients with heart diseases or renal failure and may also reflect poor diet, fluid intake, or swallowing difficulties in severe MS. 28 Indeed, another reported finding is nausea and vomiting, which could contribute to metabolic disturbance. Finally, abnormal movement was a reported finding that warrants targeted investigation, particularly given report of increased frequency of movement disorder even early in MS. 29 …”
Section: Discussionmentioning
confidence: 99%
“…5 Most of the literature showed association of PD with spinal cord lesions. 4 The presumed lesion responsible for this acute presentation of PD in our patient is the only enhancing lesion in right hemisphere located at corona radiata. An ephaptic axonal activation at a non-synaptic contact site within a partial demyelinated plaque at any level in motor pathway is considered the most likely pathophysiological explanation for PD.…”
Section: Neurosciences 2019; Vol 24 (3): 236-239mentioning
confidence: 58%
“…Typically MS has a relapsing, remitting course presenting with ataxia, hemiplegia, optic neuritis or brainstem syndromes. Movement disorders are traditionally thought to be rare in MS but recently there is more recognition of these paroxysmal disorders presenting as first episode of MS. 4,5 Their prevalence is reported less than 2% in the literature. 2 Recognition of paroxysmal phenome as an initial presentation of MS is of utmost importance as it helps not only in timely diagnosis of the primary disease but long term management with DMDs to avoid permanent brain damage as well.…”
Section: Neurosciences 2019; Vol 24 (3): 236-239mentioning
confidence: 99%
“…Focal spinal cord disease can cause a variety of involuntary movements including tonic spasms, paroxysmal or fixed focal dystonia, spinal myoclonus, spontaneous or triggered clonus, spinal tremor, and secondary restless leg syndrome (RLS) [33][34][35]. Some of these movement disorders, in particular tonic spams and paroxysmal dystonia, are thought to be more common in NMOSD than other demyelinating diseases and they can be painful [36][37][38][39].…”
Section: Tonic Spasms and Other Involuntary Movementsmentioning
confidence: 99%